The interaction between the soluble programmed death ligand-1 (sPD-L1) and PD-1+ regulator B cells mediates immunosuppression in triple-negative breast cancer - Li, Xuejiao; Du, Huan; Zhan, Shenghua; Liu, Wenting; Wang, Zhangyu; Lan, Jing; PuYang, Longxiang; Wan, Yuqiu; Qu, Qiuxia; Wang, Sining; Yang, Yang; Wang, Qin; et al. (Frontiers in Immunology, 2022)
Accumulating evidence suggests that regulatory B cells (Bregs) play important roles in inhibiting the immune response in tumors. Programmed death 1 (PD-1) and programmed death ligand 1 (PD-L1) are important molecules that maintain the balance of the immune response and immune tolerance. This study aims to evaluate the soluble form of PD-L1 and its function in inducing the differentiation of B lymphocytes, investigate the relationship between soluble PD-L1 (sPD-L1) and B-cell subsets, and explore the antitumor activity of T lymphocytes after PD-L1 blockade in coculture systems. In an effort to explore the role of sPD-L1 in human breast cancer etiology, we examined the levels of sPD-L1 and interleukin-10 (IL-10) in the serum of breast tumor patients and the proportions of B cells, PD-1+ B cells, Bregs, and PD-1+ Bregs in the peripheral blood of patients with breast tumors and assessed their relationship among sPD-L1, IL-10, and B-cell subsets. The levels of sPD-L1 and IL-10 in serum were found to be significantly higher in invasive breast cancer (IBCa) patients than in breast fibroadenoma (FIBma) patients. Meanwhile, the proportions and absolute numbers of Bregs and PD-1+ Bregs in the peripheral blood of IBCa patients were significantly higher than those of FIBma patients. Notably, they were the highest in triple-negative breast cancer (TNBC) among other subtypes of IBCa. Positive correlations of sPD-L1 and IL-10, IL-10 and PD-1+ Bregs, and also sPD-L1 and PD-1+ Bregs were observed in IBCa. We further demonstrated that sPD-L1 could induce Breg differentiation, IL-10 secretion, and IL-10 mRNA expression in a dose-dependent manner in vitro. Finally, the induction of regulatory T cells (Tregs) by Bregs was further shown to suppress the antitumor response and that PD-L1 blockade therapies could promote the apoptosis of tumor cells. Together, these results indicated that sPD-L1 could mediate the differentiation of Bregs, expand CD4+ Tregs and weaken the antitumor activity of CD4+ T cells. PD-L1/PD-1 blockade therapies might be a powerful therapeutic strategy for IBCa patients, particularly for TNBC patients with high level of PD-1+ Bregs.